TFCWS: Testing Framework for composite web services. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In every business domain Web Services are more popular solutions to implement the software. Composite web service can be created by combining basic web services. Many unreliable web services are deployed on the internet. Hence, testing is required to ensure reliability. Software testers have great challenges to test web services. Source code of web services is unavailable. The Testing Framework is used to test web services without knowledge of its internal structure. In this paper, we have proposed a Testing Framework for Composite Web Services (TFCWS). It generates report which shows the total number of test cases executed for each web service with pass or fail status of each test case. It calculates the throughput of web service and response time of each test case. We have used web services response times for analysis of TFCWS, Soap UI and Storm.